2-Phenylacetic acid-3-{(E)-2-[(E)-pyridin-3-ylmethylidene]hydrazin-1-ylidenemethyl} pyridine (2/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title 1:2 adduct, C(12)H(10)N(4)center dot-2C(8)H(8)O(2), comprises a single molecule of 2-phenylacetic acid and half a molecule of 3-pyridinealdazine; the latter is completed by crystallographic inversion symmetry. In the crystal, molecules are connected into a three-component aggregate via O-H center dot center dot center dot N hydrogen bonds. As the carboxyl group lies above the plane through the benzene ring to which it is attached [C-C-C-C = 62.24 (17)degrees] and the 4-pyridinealdazine molecule is almost planar (r.m.s. deviation of the 16 non-H atoms = 0.027 angstrom), the overall shape of the aggregate is that of a flattened extended chair. Layers of these aggregates are connected by C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions and stack parallel to (220).